Is Action Planning Helpful for Smoking Cessation? Assessing the Effects of Action Planning in a Web-Based Computer-Tailored Intervention. (24th August 2015) - Bolman, Catherine; Eggers, Sander Matthijs; van Osch, Liesbeth; Te Poel, Fam; Candel, Math; de Vries, Hein
Abstract : Background and objectives : The aim of this study was to examine the efficacy of a web-assisted computer-tailored smoking cessation intervention, an action planning (AP) intervention in which potential quitters were encouraged to form action plans (e.g., plan a quit date) and execute them (e.g., remove ashtrays). We also investigated whether the AP intervention resulted in more AP and plan execution than a similar, control intervention without the supplementary AP component. Methods : In a randomized controlled trial, the AP intervention ( N = 977) was compared with the control intervention ( N = 1, 005) in terms of self-reported continued abstinence (CA) and point prevalence abstinence (PPA) six months after baseline. AP, plan execution, and opinion of the intervention were measured one month after baseline. Results : Complete-case logistic regression analysis showed that the AP intervention had a significant effect on CA (OR = 2.01; CI 1.08–3.84, p = .02), whereas intention-to-treat analysis showed a borderline significant effect (OR = 1.68; CI .96–2.92, p = .07). Sixteen percent of the experimental group achieved CA compared to 10% of the control group. The AP intervention had no effect on PPA. The experimental group also showed significantly more AP and plan execution at one month. Execution of plans was associated with smoking cessation. Conclusions : The effects of the AP intervention on CA, AP, and execution of plans were encouraging. The potential for widespread use of web-based interventions means that even small behavioral effects may have an impact on public health. We recommend that the intervention be intensified and improved.